Bi-directional high speed domain wall motion in perpendicular magnetic anisotropy Co/Pt double stack structures - Sethi, Pankaj (2018)
We report bi-directional domain wall (DW) motion along and against current flow direction in Co/Pt double stack wires with Ta capping. The bi-directionality is achieved by application of hard-axis magnetic field favoring and opposing the Dzyloshinskii-Moriya interaction (DMI), respectively. The speed obtained is enhanced when the hard-axis field favors the DMI and is along the current flow direction. Co/Pt double stack is a modification proposed for the high spin-orbit torque strength Pt/Co/Ta stack, to improve its thermal stability and perpendicular magnetic anisotropy (PMA). The velocity obtained reduces with increase in Pt spacer thickness due to reduction in DMI and enhances on increasing the Ta capping thickness due to higher SOT strength. The velocity obtained is as high as 530 m/s at a reasonable current density of 1 × 1012 A/m2 for device applications. The low anisotropy of the device coupled with the application of hard-axis field aids the velocity enhancement by preventing Walker breakdown.